Assessing the Role of Economic, Financial, and Institutional Dynamics on CO2 Emissions: Comparative Analysis of OECD and Western Balkan Regions - Beka, Artenisa; Bilalli, Argjira; Gara, Atdhetar (Ekonomika, 2024)
The main purpose of this research is assessing dynamics of economic, financial, and institutional developments on CO2 emissions for the period of twelve years, namely from 2010 to 2022, applying a comparative approach between 38 OECD and 5 Western Balkan countries. Further, the topic was chosen considering the role of environment and the degradation may cause economic, financial, and institutional developments. To specify this impact/correlation, secondary data was extracted from reliable sources. Additionally, the methodological approach in this study employs standard regression techniques adapted for panel data, including OLS, fixed effects (FE), random effects (RE), and Hausman–Taylor model instrumental variables IV. The analysis includes especially the Western Balkans and the OECD countries as well as their comparative aspect, and findings indicate the significant roles of inflation, business freedom, and notably, political stability in influencing CO2 emissions have been highlighted.The study’s contribution to literature is significant in two main ways. Firstly, it addresses a research gap by introducing a unique dataset and methodology for a specific time. Secondly, the importance of comparing the OECD countries with 5 Western Balkan countries is highlighted, providing valuable insights into differing economic, social, and environmental dynamics. This comparative approach of the study offers a practical framework that policymakers can use to develop effective strategies.
Keywords: Economic; Financial and Institutional Developments; Environment